Hubungan Pendidikan Orang Tua dengan Tingkat Kemandirian Personal Hygiene Saat Menstruasi Pada Remaja Dengan Intellectual Disability - Dwiyati, Dwiyati; Arumti Sudarno, Himas (Journal of Holistic Nursing Science, 2019)
Teenagers with intellectual disability have delays and limitations related to the developmental area in adaptation skills such as self-care including personal hygiene during menstruation.They need continuousstimulation in order to increase their independence in performing personal hygiene. The parents’ style in educating their children cannot be separated from their educational background. Higher parents education is expected to be able to set their children in performing their personal hygiene during menstruation This research aimed to know the correlation between parents’ education and independence of personal hygiene during menstruation among adolescent with intellectual disability in Marsudi Putra Outstanding School Bantul. This type was quantitative research used cross sectional approach. The study population was parents who have intellectual disability children who have menstruated in Marsudi Putra Outstanding School as many 35 respondents, with a total sampling sampling technique as many 35 respondents. Data collection used closed questionnaire. Data analysis with spearmen test. The majority of respondents were high school educated as many 11 respondents (31.4%), while the level of independence of personal hygiene during menstruation in intellectual disability children was mostly in independent category as many 17 children (48.6%). There was a significant correlation between parents’ education and independence level of personal hygiene during menstruation among teenagers with intellectual disability in Marsudi Putra Special Education School with p-value of 0,000 (p<0,05) with high proximity of correlation (r=0,776).Thank you to the students, teachers, head master of Marsudi Putra Special Education School who have helped in the data collection process and all parties so that this research can be completed.